Avaliação do programa de integridade e Compliance do estado do Paraná: biênio 2019/2020 - Grego, Ricardo Gambini (2021)
This research aims to analyze the evaluations of managers, government employees, and citizens about the actions and development of the Integrity and Compliance Program of the State of Paranáin its initial implementation phase, in addition to presenting a simplified monitoring model for such program. The methodology used can be characterized as a descriptive, documentary, bibliographic, exploratory and, when analyzing the approach of the study, it is understood as qualitative, in the first stage, and quantitative, in the second stage, or analysis stage, as techniques for crossing and comparing data were used in order to meet the proposed objectives. To perform the data analysis procedures, the statistical computer program SPSS was used and, in sequence, a descriptive analysis of the data was performed, followed by a cross-section analysis with data crossing, aiming to understand the target audience perceptions, highlighting its characteristics. From the treatment and analysis of the information, it has been characterized as expected results, the evidence that the Integrity and Compliance Program of the State of Paraná has a good or excellent evaluation of the target population, in addition to obtaining proof of similar characteristics of the State Program with those of other programs and/or actions of other bodies or entities, whether public or private, national or international, which had a good and relevant performance in the locations where they were applied.